Saccharopolyspora gloriosae sp. nov., an endophytic actinomycete isolated from the stem of Gloriosa superba L. - Qin, Sheng; Chen, Hua-Hong; Klenk, Hans-Peter; Kim, Chang-Jin; Xu, Li-Hua; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2010)
A Gram-stain-positive, aerobic actinomycete, strain YIM 60513T, was isolated from the stem of Gloriosa superba L. collected from tropical rainforest at Xishuangbanna, Yunnan Province, south-west China. 16S rRNA gene sequence analysis indicated that strain YIM 60513T belonged to the genus Saccharopolyspora and was closely related to Saccharopolyspora gregorii NCIB 12823T (99.1 % similarity) and Saccharopolyspora cebuensis SPE 10-1T (97.3 % similarity). Data for the predominant quinone [MK-9(H4)], major fatty acids (iso-C16 : 0, anteiso-C17 : 0 and C17 : 1 cis9) and G+C content of the genomic DNA (71.6 mol%) were similar to those for members of the genus Saccharopolyspora. The level of DNA–DNA relatedness between strain YIM 60513T and S. gregorii NCIB 12823T was 43 %. The combination of phylogenetic analysis, phenotypic differences, chemotaxonomic characteristics and DNA–DNA hybridization data supported the view that strain YIM 60513T should be distinguished from S. gregorii NCIB 12823T and S. cebuensis SPE 10-1T. Strain YIM 60513T therefore represents a novel species of the genus Saccharopolyspora, for which the name Saccharopolyspora gloriosae sp. nov. is proposed. The type strain is YIM 60513T (=KCTC 19243T =CCTCC AA 207006T).